Checklist and new records of Christmas Island fishes: the influence of isolation, biogeography and habitat availability on species abundance and community composition - Hobbs, Jean-Paul; Newman, Stephen; Mitsopoulos, G.; Travers, M.; Travers, M.; Skepper, C.; Gilligan, J.; Allen, G.; Choat, H.; Ayling, A. (Raffles Museum of Biodiversity Research, 2014)
Christmas Island (Indian Ocean) is an oceanic high island that is situated 300 km southwest of Java, Indonesia. From 2010 to 2014, the fish community of Christmas Island was surveyed using underwater visual surveys for shallow water (0–60 m) fishes, and line fishing (bottom fishing and trolling) for deepwater (60–300 m) and pelagic fishes. Forty-seven new records (from 22 families) were identified, thereby increasing the total number of fishes described from Christmas Island to 681 (from 91 families). Notable new records include the first records for the families Alopiidae, Anomalopidae, Muraenesocidae, Tetrarogidae and Trichonotidae, and the first reports of Pacific Ocean species Plectranthias yamakawai, and Polylepion russelli in the Indian Ocean. The ten most species-rich families accounted for 58% of the community and included: Labridae (13%), Pomacentridae (8%), Epinephelidae (6%), Acanthuridae (5%), Chaetodontidae (5%), Muraenidae (5%), Gobiidae (5%), Blenniidae (4%), Apogonidae (4%) and Scorpaenidae (3%). The majority (89%) of species inhabit shallow coral reefs, with deep reefs (60–300 m) and pelagic waters only accounting for 7% and 2% of fish community. Approximately 76% of thefishes are widespread Indo-Pacific species, 12% are Pacific Ocean species, 5% are circumtropical, 4% are Indian Ocean species and approximately 1% are endemic. Abundance surveys revealed that endemic species, and species at the edge of their geographic range, do not conform to terrestrial-based predictions of low abundance. The structure and composition of the Christmas Island fish community is influenced by three main factors. Firstly, the isolation of the island means that fishes with poor dispersal abilities (e.g., syngnathids) are underrepresented. Secondly, thebiogeographic position of the island results in a unique mixing of Indian and Pacific Ocean species. Thirdly, the lack of lagoonal habitats means that fishes that use these habitats (e.g., ophichthids, lethrinids, epinephelids) are underrepresented or have low abundance.